Estimates of the 2015 global and regional disease burden from four foodborne metals - arsenic, cadmium, lead and methylmercury - Herman J Gibb; Aaron Barchowsky; David Bellinger; P Michael Bolger; Clark Carrington; Arie H Havelaar; Shilpi Oberoi; Yu Zang; Keri O'Leary; Brecht Devleesschauwer (Environ Res, 2019)
The impact of foodborne metals on the burden of disease has been largely overlooked, in comparison to the attention on acute diseases associated with infectious foodborne agents. Four articles in this special section describe in detail the burden of disease from foodborne lead, methylmercury, arsenic, and cadmium. Ingested lead and methylmercury are causally associated with lifelong intellectual disability. Long term ingestion of arsenic is causally associated with an increased risk of cancer. Long term ingestion of cadmium is causally associated with an increased risk of late stage chronic kidney disease. This article presents an overview of the burden of disease from these four foodborne metals and discusses them in the context of the World Health Organization's initiative to estimate the global burden of foodborne disease. The results indicate that in 2015, ingestion of arsenic, methylmercury, lead, and cadmium resulted in more than 1 million illnesses, over 56,000 deaths, and more than 9 million disability-adjusted life years (DALYs) worldwide. The greatest impact on DALYs was in the Western Pacific B subregion. All of the metals were found to have high DALYs per case in comparison with other foodborne disease agents, including infectious and parasitic agents. In addition, lead, arsenic, and methylmercury were found to have high DALYs per 100,000 population in comparison to other foodborne disease agents.